Authentic materials in learning English - N. A. Narykova; N. A. Simonova (Вестник Северо-Кавказского федерального университета)
The article is devoted to the study of the practical significance of the use of authentic materials as an effective supplement to prescribed textbooks in order to increase the level of knowledge of students and significant development of language skills in the process of teaching English. The scientific novelty of the study is to determine the advantages of using authentic materials in foreign language classes for both students and teachers. According to the results of the study, it was revealed that the use of authentic material has a positive effect on the motivation of learning a foreign language and is a publicly available educational element that can solve socio-cultural and foreign-language professional tasks, as well as provides teachers with the opportunity to apply various learning strategies using modern technologies.